The Effects of Commitment of Non-Family Employees of Family Firms from the Perspective of Stewardship Theory - Vallejo, Manuel Carlos (Journal of business ethics, 2009)
Although commitment is one of the attributes of family firms of continuing interest to researchers, they almost always study it from the perspective of the owning family. In the current work, we analyze the commitment of the non-family employees. We propose a model of commitment, with the aim of studying the implications that this variable may have for family businesses. We study both the aspects on the basis of the approaches of Meyer and Allen’s three-component model of organizational commitment and stewardship theory. Results show that the identification level of non-family employees positively and significantly influences the profitability and the survival or continuity of family-owned businesses. At the same time that their involvement level positively and significantly influences the survival or continuity of family-owned businesses.